Fishing for trouble - Logan, Elizabeth, 1937- (Logan, Elizabeth, 1937- Alaskan diner mystery., 2020)
When a local fisherman is found drowned in Wonder Lake, chef Charlotte "Charlie" Cooke is asked to investigate, and as she trawls for clues, she must work with a local journalist to net the killer.